Religious policy in Uzbekistan: Between liberalisation, state ideology and Islamisation - Andrea Schmitz (Stiftung Wissenschaft und Politik (SWP), 2023)
The religious policy innovations that Uzbekistan's President Mirziyoyev has initiated in the name of liberalisation and reform continue the policies of his predecessor in key aspects. Under the motto 'enlightenment against ignorance', state influence over the religious knowledge taught in educational and research institutions has been strengthened. The country's Islamic heritage is proactively used for representative purposes and held up as an integral part of national culture. The religious policy measures that amount to a 'secularisation' of Islam through scientification and musealisation do not reach large sections of society. For the ordinary believer, Islam is not a science but a matter of belief, a system of rules and convictions that guides the way they live. The liberalisation of the media landscape means that religious advice is available in abundance. It often includes propaganda transporting illiberal ideas, but the state intervenes only selectively. The liberalisation of religious policy has resulted in a growing Islamisation of the population. The authoritarian state headed by President Mirziyoyev is thus being consolidated. Repression remains the means of choice should Islamic milieus seriously challenge the secular state.
Keywords: 320; Uzbekistan; President Mirziyoyev; Islam; Imam; Sharia; Muslim authorities; Koran; secularism; religious education; Islamic Movement of Uzbekistan (IBU); Directorate of Muslims of Uzbekistan (DMU)